Plasma modes in capacitively coupled superconducting nanowires - Latyshev, Alex; Semenov, Andrew G.; Zaikin, Andrei D. (Beilstein Journal of Nanotechnology, 2022)
We investigate plasma oscillations in long electromagnetically coupled superconducting nanowires. We demonstrate that in the presence of inter-wire coupling plasma modes in each of the wires get split into two “new” modes propagating with different velocities across the system. These plasma modes form an effective dissipative quantum environment interacting with electrons inside both wires and causing a number of significant implications for the low-temperature behavior of the systems under consideration.
Keywords: plasma modes; quantum fluctuations, quantum phase slips; superconducting nanowires